FLUX AND GRAIN SIZE VARIATION OF EOLIAN DUST AS A PROXY TOOL FOR THE PALEO-POSITION OF THE INTERTROPICAL CONVERGENCE ZONE IN THE NORTHEAST PACIFIC - Hyeong K.; Yoo C.M.; Kim J.; Chi S.-B.; Kim K.-H. (My University, 2006)
A 328 cm-long piston core (KODOS 02-01-02) collected from the northeast equatorial Pacific at 16°12′N, 125°59′W was investigated for eolian mass fluxes and grain sizes to test these proxies as a tool for the paleo-position of the Intertropical Convergence Zone (ITCZ). The eolian mass fluxes of the lower interval below 250 cm (15.5-7.6 Ma) are very uniform at 5 ± 1 mg/cm2/103 yr, while those of the upper interval above 250 cm (from 7.6 Ma) are over 2 times higher than the lower interval at 12 ± 1 mg/cm2/103 yr. The median grain size of the eolian dusts in the lower interval increases from 8.4φ{symbol} to 8.0φ{symbol} downward, while that of the upper interval varies in a narrow range from 8.8φ{symbol} to 8.6φ{symbol}. The determined values compare well in magnitude to those of central Pacific sediments for the upper interval and equatorial and southeast Pacific sediments for the lower interval. This result suggests a possibility that the study site had been under the influence of southeast trade winds at its earlier depositional period due to the northerly position of the ITCZ, and subsequently of the northeast trade winds for a later period when the upper sediments were deposited. This interpretation is consistent with a mineralogical and geochemical study published elsewhere that assigned the provenance of the study core dust to Central/South America for the lower interval and to Asia for the upper interval. This study suggests that the distinct differences in eolian mass flux and grain size observed across the ITCZ can be used to trace the paleo-latitude of the ITCZ. © 2006 Elsevier B.V. All rights reserved.
Keywords: EOLIAN DUST; GRAIN SIZE; INTERTROPICAL CONVERGENCE ZONE; MASS ACCUMULATION RATE; NORTHEAST PACIFIC; PELAGIC SEDIMENTS